SoxE function in vertebrate nervous system development. - Stolt, Claus; Wegner, Michael (International Journal of Biochemistry & Cell Biology, 2010)
Sox8, Sox9, and Sox10 as transcription factors of subgroup E of the Sox protein family are essential for many aspects of nervous system development. These SoxE proteins are already required for the initial neural crest induction, but also guarantee survival and maintenance of pluripotency in migrating neural crest stem cells. SoxE proteins are furthermore key regulators of glial specification in both the peripheral and the central nervous systems. At later stages of development, Sox10 plays crucial roles in Schwann cells and oligodendrocytes for terminal differentiation and myelin formation. In both glial cell types, Sox10 controls directly the expression of genes encoding the major myelin proteins. SoxE proteins are well-integrated components of regulatory networks and as such modulated in their activity by cooperating or antagonistic transcription factors such as SoxD or various bHLH proteins. The multiple functions in peripheral and central nervous system development also link SoxE proteins to various human diseases and identify these proteins as promising targets of future therapeutic approaches. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.med.IB.LPCIPDBI.soxefu
Keywords: Astrocyte; Differentiation; Oligodendrocyte; Schwann cell; Specification